The indigenous cattle of Ethiopia. Part II - Alberro, M.; Haile-Mariam, S. (1982)
In any country, a good, basic knowledge of available genetic resources is essential for programmes of livestock conservation, selection and improvement. This study describes different indigenous cattle breeds of Ethiopia. Their physical characteristics, geographic distribution and production potentials are discussed.